IFS Consisting of TS-IF Contraction Mapping in the Intuitionistic Fuzzy Metric Spaces - Priyanka, S. C. Shrivastava, R. Shrivastava (International Journal of Advanced Science and Technology, 2020)
Fractals is an interesting area of research that provides many research possibilities in numerous areas of science and mathematics. The use of IFS is one of the more interesting and profound extension in the building of fractal sets. We realize that, instances of fractals are forthcoming from theory of fixed point principlefor operators (single- valued operator), using the commonly named fractal operators. Otherwise, the broad setting for examination of attractors is the condition of contraction mappings on complete metric space. Theory ofTS-IF contractive mapping was introduced and studied by T. K. Samanta et.al. and notion of IFMS was introduced by Park. In this present article, we combine these two elements by studying IFS consisting of TS-IF contractive mapping on the framework of IFMS. More precisely, we obtain a variety of results for IFS with the use of TS-IF contractive map in the new structure of IFMS. Further, our results are generalization in some recent aspects and analogous relevant with HB operator in the general setting.